HIV, multidrug-resistant TB and depressive symptoms: when three conditions collide - Mrinalini Das; Petros Isaakidis; Rafael Van den Bergh; Ajay MV Kumar; Sharath Burugina Nagaraja; Asmaa Valikayath; Santosh Jha; Bindoo Jadhav; Joanna Ladomirska (Taylor & Francis Group, 2014)
Background: Management of multidrug-resistant TB (MDR-TB) patients co-infected with human immunodeficiency virus (HIV) is highly challenging. Such patients are subject to long and potentially toxic treatments and may develop a number of different psychiatric illnesses such as anxiety and depressive disorders. A mental health assessment before MDR-TB treatment initiation may assist in early diagnosis and better management of psychiatric illnesses in patients already having two stigmatising and debilitating diseases. Objective: To address limited evidence on the baseline psychiatric conditions of HIV-infected MDR-TB patients, we aimed to document the levels of depressive symptoms at baseline, and any alteration following individualized clinical and psychological support during MDR-TB therapy, using the Patient Health Questionnaire-9 (PHQ-9) tool, among HIV-infected patients. Design: This was a retrospective review of the medical records of an adult (aged >15 years) HIV/MDR-TB cohort registered for care during the period of August 2012 through to March 2014. Results: A total of 45 HIV/MDR-TB patients underwent baseline assessment using the PHQ-9 tool, and seven (16%) were found to have depressive symptoms. Of these, four patients had moderate to severe depressive symptoms. Individualized psychological and clinical support was administered to these patients. Reassessments were carried out for all patients after 3 months of follow-up, except one, who died during the period. Among these 44 patients, three with baseline depressive symptoms still had depressive symptoms. However, improvements were observed in all but one after 3 months of follow-up. Conclusion: Psychiatric illnesses, including depressive symptoms, during MDR-TB treatment demand attention. Routine administration of baseline mental health assessments by trained staff has the potential to assist in determining appropriate measures for the management of depressive symptoms during MDR-TB treatment, and help in improving overall treatment outcomes. We recommend regular monitoring of mental health status by trained counsellors or clinical staff, using simple, validated and cost-effective tools.